A sensitive cytosensor for sialic acid assay based on dual signal amplification by functionalized carbon nanospheres and enzymatically produced polyaniline. Issue 9 (7th May 2015) - Liu, Kai; Sun, Qianqian; Zhu, Linling; Feng, Chongchong; Zhang, Junying; Wang, Ya; Zhang, Fan; Xu, Zhiai; Zhang, Wen
<x xml:space="preserve">Abstract</x> A new strategy for cell surface sialic acid assay and electrochemical cytosensing integrating specific carbohydrate identification and enzymatic catalysis.